2012
DOI: 10.1007/s10802-012-9689-5
|View full text |Cite|
|
Sign up to set email alerts
|

Motor, Emotional, and Cognitive Empathy in Children and Adolescents with Autism Spectrum Disorder and Conduct Disorder

Abstract: It is unclear which aspects of empathy are shared and which are uniquely affected in autism spectrum disorder (ASD) and conduct disorder (CD) as are the neurobiological correlates of these empathy impairments. The aim of this systematic review is to describe the overlap and specificity of motor, emotional, and cognitive aspects of empathy in children and adolescents with ASD or CD. Motor and cognitive empathy impairments are found in both ASD and CD, yet the specificity seems to differ. In ASD facial mimicry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 124 publications
6
81
0
3
Order By: Relevance
“…Finally, the BES-C could prove useful for studying empathy from a new perspective, particularly in children who display impaired empathy, such as those with autism spectrum disorder (e.g., Bons et al, 2013;Schwenck et al, 2012). This would extend the current literature on empathy in middle childhood.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, the BES-C could prove useful for studying empathy from a new perspective, particularly in children who display impaired empathy, such as those with autism spectrum disorder (e.g., Bons et al, 2013;Schwenck et al, 2012). This would extend the current literature on empathy in middle childhood.…”
Section: Discussionmentioning
confidence: 96%
“…Our results further suggest that poorer ability to feel other's fear in those with ADHD maybe a pathway from COMT to aggression. The importance of empathy skills in relation to psychopathology has become increasingly recognised and is an emerging area of neuroscience (Panksepp & Panksepp, 2013); empathy deficits have been proposed as an explanatory mechanism underlying social impairments characteristic of many different psychiatric disorders including Conduct Disorder and Autism Spectrum Disorders (ASD)(Bons et al., 2013). The present study supports findings that understanding (cognitive empathy) and feeling (affective empathy) others' emotions can be meaningfully disaggregated (Bons et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, past studies showed weak to moderate correlations between emotion and cognitive functioning, suggesting that the two operate at different brain levels [21]. Decety and Meyer [22] attempted to explain the difference between the three social information processing aspects in terms of two different neural pathways that are running in parallel and interrelated, that is, a bottom-up process based on emotion perception-action coupling and potentially underpinned by mirror neuron systems and a top-down meta-cognitive executive regulatory control that modulates lower-emotion perception-action mechanisms.…”
Section: Literature Reviewmentioning
confidence: 96%